Hodnocení investičního záměru - Kroutilová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Diplomová práce se zaměřuje na hodnocení investičního záměru výstavby nového bytového komplexu v Brně a následně zhodnocení výnosnosti projektu pro danou společnost. Na základě literární rešerše jsou zpracovány teoretické poznatky, které jsou východiskem pro zpracování investičního záměru. Za použití statistických metod a analýz je vyhodnocena efektivnost investičního projektu a jeho rizika. Závěrem jsou vyhodnocena získaná data, dle kterých lze říci, zda investiční záměr doporučit či nikoliv.

The diploma thesis focuses on the evaluation of the investment plan for the construction of a new residential complex in Brno and the subsequent evaluation of the profitability of the project for the company. On the basis of the literary research, theoretical knowledge is elaborated, which is the starting point for processing the investment plan. The effectiveness of the investment project and its risks are evaluated using statistical methods and analyzes. In conclusion, the obtained data are evaluated, according to which it is possible to say whether or not to recommend the investment plan.
Evaluation of Investments Project
Keywords: investice; hodnocení investice; efektivita investice; čistá současná hodnota; rizikovost; developerský projekt; investment; evulation of the investment; efficiency of the investment; net present value; risk; developer project